Why HALO 301 Failed and Implications for Treatment of Pancreatic Cancer - Nausheen Hakim; Rajvi Patel; Craig Devoe; Muhammad W. Saif (Pancreas, 2019)
Survival rates for pancreatic cancer (PC) remain dismal. Current standard of care treatment regimens provide transient clinical benefit but eventually chemoresistance develops leading to poor outcomes. PC is a relatively chemoresistant tumor and one of the explanations for this is attributed to desmoplasia that impedes drug delivery. Based on this, stromal modifying agent such as Pegvorhyaluronidase alfa (PEGPH20) was developed and investigated in phase I-III studies. Although phase I-II studies showed promising results in patients with high hyaluronic acid (HA) expressing tumors, the phase III HALO 301 study failed to miss it’s primary endpoint and further development of PEHPH20 is halted. This failure implies that targeting desmoplasia alone is not sufficient and other intrinsic factors such as lack of significant neoantigens, low tumor mutational burden, and epithelial to mesenchymal transition may be at play. It is also important to consider that although the tumor stroma may be a physical bar-rier hampering drug delivery, it may also have protective effects in restraining tumor growth and progression. Further studies in molecular biology to better characterize the complex interaction between the microenvironment and cancer cells are warranted.